Systematic Review With Network Meta-Analysis. Issue 1 (January 2015) - Zhu, Gui-Qi; You, Jie; Shi, Ke-Qing; He, Sun-Yue; Wang, Li-Ren; Chen, Yong-Ping; Braddock, Martin; Zheng, Ming-Hua; Rantanen., Tuomo
<x xml:space="preserve">Abstract</x> Abstract There are 5 major adjuvant chemotherapies (ACTs) for hepatic metastases for colorectal cancer; however, the optimal treatment regimen remains inconclusive. Here, we aim to compare these therapies in terms of patient survival rate, intrahepatic recurrence rate, and adverse events. Different databases were searched for controlled trials up to June 30, 2014. The pooled hazards ratios for death and odds ratios (ORs) for intrahepatic recurrence and adverse events were estimated. A mean ranking and the probability of optimal therapeutic regime was obtained for each treatment analyzed in the network meta-analysis. Eleven eligible articles were included. Systemic chemotherapy (SCT) was ranked the most efficacious intervention among ACTs in both 1-year and 5-year survival; however, no statistical difference could be determined. Combination of bevacizumab (BEV) and hepatic arterial infusion (HAI) plus SCT was the most effective in preventing intrahepatic recurrence when compared with HAI alone (OR 1.21, 95% confidence interval [CI] 0.01–131.12), SCT (OR 2.37, 95% CI 0.03–234.16), HAI plus SCT (OR 0.97, 95% CI 0.03–35.30), SCT plus irinotecan (OR 1.01, 95% CI 0.00–278.14) and observation alone (OR 0.83, 95% CI 0.01–59.53). BEV and HAI plus SCT provided the least survival benefit after both 1 and 5 years compared with remaining therapies, and also was ranked the regiment with the least favorable adverse event profile among ACTs. SCT may be the most efficacious intervention, however, the potential benefit should be carefully considered with the regime's associated toxicities. Combination of BEV and HAI plus SCT was effective in preventing intrahepatic relapse but was associated with the highest risk for adverse events in patients with resected hepatic metastases for colorectal cancer.